(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Postpartum haemorrhage (PPH) is the leading cause of maternal death worldwide. It is a preventable event in abdominal and vaginal deliveries. Preventive measures include prophylactic drug use to aid uterine contraction after delivery, thus avoiding severe blood loss and reducing maternal morbidity and mortality. Carbetocin is a synthetic analogue of oxytocin with a half-life approximately 4-10 times longer than that reported for oxytocin. It combines the safety and tolerability profile of oxytocin with the sustained uterotonic activity of injectable ergot alkaloids. Objectives: The objective was to compare the effectiveness of carbetocin and oxytocin when administered after uncomplicated cesarean section (CS) for the prevention of postpartum haemorrhage. Study Design: This is a prospective randomized controlled study comparing the use of carbetocin and oxytocin for the prevention of postpartum haemorrhage following caesarean section of patients admitted at Obstetrics & Gynaecology department of Dhaka National Medical Institute Hospital (DNMIH) from January 2014 to December 2014. Materials and Methods: A total of 240 patients undergoing caesarean section were randomized to carbetocin (N=120) and oxytocin (N=120) for the prevention of postpartum haemorrhage and analyzed by intention to treat. Women in the carbetocin group (Group A) received a IV bolus of 100μg carbetocin and women in the oxytocin (control) group (Group B) received a IV bolus of 10 IU oxytocin. Baseline demographic and obstetric profile, indications for CS, estimated blood loss, hemoglobin, need for uterine massage, additional uterotonics, uterine tone and involution were compared immediate post-operative and 2 hours after. Results: Baseline profiles were similar between the two groups. Post-operatively, hemoglobin levels in the carbetocin group were statistically significant and were associated with lesser need for additional uterotonic agents, uterine massage and a well contracted uterus immediate post-operative and 2 hours thereafter. The estimated blood loss was significantly lower in the carbetocin group and blood transfusion required more in oxytocin group however, the two groups did not significantly differ in terms of post-operative blood pressure. Conclusion: Carbetocin as an uterotonic agent is an acceptable alternative for the prevention of postpartum bleeding in cesarean section. A cost-benefit analysis is mandated. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 40-46